(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Instructional delivery has been under series of modifications since the advent of Information and Communication Technology (ICT). Particularly, with the need to shapeclassrooms to match the 21st century job demands, the use of technology has become compulsory for teachers to incorporate in the classroom. This study ascertained the level of application of blended learning pedagogical design by business educators in tertiary institutions in Anambra State. One research question guided the study and two null hypotheses were tested. Descriptive survey research design was adopted for the study. The population of the study comprised 99 business educators from public tertiary institution in Anambra State. No sampling was done due to the relatively small size of the population. The instrument for data collection was a structured questionnaire titled “Level of application of Blended-learning Pedagogical Design Questionnaire” (LABPDQ) which was validated by three experts. Cronbachalpha was used to determine the reliability of the instrument and it yielded reliability coefficient of 0.89. The researchers together with two research assistants collected data for the study using direct approach method and 91% return rate was recorded. Mean and standard deviation were used to answer the research question while t-test was used in testing the hypotheses at 0.05 level of significance. The findings of the study revealed among others that business educators apply blended learningpedagogical design at a moderate level in tertiary institutions in Anambra State. Based on the findings, it was recommended among others that administrators of business education programmes should regularly organize in-service training for lecturers on current trends in the application of blended learning pedagogical design in the classrooms. Lecturers should from time to time avail themselves the opportunity to get acquainted with the state-of-theart technology by attending the training programmes, workshops and seminars.